Growth Differentiation Factor 5 Improves Neurogenesis and Functional Recovery in Adult Mouse Hippocampus Following Traumatic Brain Injury - Wu, Hongjie; Li, Jing; Xu, Dongxiao; Zhang, Qiansheng; Cui, Tao (Frontiers in Neurology, 2018)
The aim of this study was to investigate the therapeutic effect of growth differentiation factor 5 (GDF-5) on traumatic brain injury (TBI) in mice. We utilized a controlled cortical impact to establish a mouse TBI model, and then stereotaxically administered 25 or 100 ng GDF-5 into the bilateral hippocampal dentate gyrus (DG) of each of the animals. Seven days after the injury, some of the animals were sacrificed for immunohistochemical and immunofluorescence examination of 5-bromo-2´-deoxyuridine (BrdU), Sox-2, doublecortin (DCX) and phosphorylated cAMP response element binding protein (p-CREB). Dendrite quantification was also performed using DCX positive cells. Activation of newborn neurons was assessed 35 days after the injury. The remaining animals were subjected to open field, Y maze and contextual fear conditioning tests two months after TBI. As a result, we found that post-injury stereotaxical administration of GDF-5 can improve neural stem cell proliferation and differentiation in the DG of the hippocampus, evidenced by the increase in BrdU, Sox-2, and DCX-labelled cells, as well as the improvement in dendrite arborization and newborn neuron activation in response to GDF-5 treatment. Mechanistically, these effects of GDF-5 may be mediated by the CREB pathway, manifested by the recovery of TBI-induced dephosphorylation of CREB upon GDF-5 administration. Behavioral tests further verified the effects of GDF-5 on improving cognitive and behavioral dysfunction after TBI. Collectively, these results reveal that direct injection of GDF-5 into the hippocampus can stimulate neurogenesis and improve functional recovery in a mouse TBI model, indicating the potential therapeutic effects of GDF-5 on TBI.